Anti-HLA Class II Antibodies Are the Most Resistant to Desensitization in Crossmatch-positive Living-donor Kidney Transplantations: A Patient Series - Annelies E. de Weerd, MD, PhD; Dave L. Roelen, PhD; Michiel G.H. Betjes, MD, PhD; Marian C. Clahsen-van Groningen, MD, PhD; Geert W. Haasnoot, BSc; Marcia M.L. Kho, MD, PhD; Marlies E.J. Reinders, MD, PhD; Joke I. Roodnat, MD, PhD; David Severs, MD; Gonca E. Karahan, PhD; Jacqueline van de Wetering, MD, PhD (Transplantation Direct, 2024)
Background. In HLA-incompatible kidney transplantation, the efficacy of desensitization in terms of anti-HLA antibody kinetics is not well characterized. We present an overview of the course of anti-HLA antibodies throughout plasma exchange (PE) desensitization in a series of crossmatch-positive patients. Methods. All consecutive candidates in the Dutch HLA-incompatible kidney transplantation program between November 2012 and January 2022 were included. The eligibility criteria were a positive crossmatch with a living kidney donor and no options for compatible transplantation. Desensitization consisted of 5–10 PE with low-dose IVIg. Results. A total of 16 patient-donor pairs were included. Patients had median virtual panel-reactive antibody of 99.58%. Cumulative donor-specific anti-HLA antibody (cumDSA) mean fluorescence intensity (MFI) was 31 399 median, and immunodominant DSA (iDSA) MFI was 18 677 for class I and 21 893 for class II. Median anti-HLA antibody MFI response to desensitization was worse in class II as compared with class I (P < 0.001), particularly for HLA-DQ. Class I cumDSA MFI decreased 68% after 4 PE versus 53% in class II. The decrease between the fifth and the 10th PE sessions was modest with 21% in class I versus 9% in class II. Antibody-mediated rejection occurred in 85% of patients, with the iDSA directed to the same mismatched HLA as before desensitization, except for 3 patients, of whom 2 had vigorous rebound of antibodies to repeated mismatches (RMMs). Rebound was highest (86%) in RMM-DSA with prior grafts removed (transplantectomy n = 7), lower (39%) in non-RMM-DSA (n = 30), and lowest (11%) for RMM-DSA with in situ grafts (n = 5; P = 0.018 for RMM-DSA transplantectomy versus RMM-DSA graft in situ). With a median follow-up of 59 mo, 1 patient had died resulting in a death-censored graft survival of 73%. Conclusions. Patients with class II DSA, and particularly those directed against HLA-DQ locus, were difficult to desensitize.